Business model dynamics from interaction with open innovation - Montserrat Pe\~narroya-Farell; Francesc Miralles (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In today's competitive environment, firms face strong challenges. We live in a volatile, uncertain, complex and ambiguous (VUCA) environment where open innovation is a strategic choice and, on top of that, the COVID-19 pandemic has emphasized most of these disrupting forces. Incumbent companies must act strategically by adapting their business model to minimize the risk and to capture the new value that emerges. This article intends to contribute to the development of the nascent stream of research that seeks to understand the evolution of Business Models through time - known as Business Model Dynamics (BMD) - and explores how to better align this evolution to the implementation settings of strategy. This exploratory study is built upon a meta-synthesis approach to identify, analyze, and clarify how academics have dealt with the three terms used in the Business Model Dynamics research strand: Business Model Innovation, Business Model Adaptation, and Business Model Evolution. The results of the meta-synthesis show that a disambiguation of concepts is necessary as, from an organizational learning point of view, it is required to provide a better connection between strategic value appropriation and changes on Business Models. This article contributes to the researcher and practitioner's literature on Business Model Dynamics offering a clear and rigorous definition of each term from a strategic point of view, thus preventing the conceptual incoherence and their reiterated wrong use as synonyms.
Keywords: 650; open innovation; BMA; BMI; business model adaptation; business model dynamics; business model evolution; business model innovation; change management